Romulus, My Father - Roxburgh, Richard; Bana, Eric; Potente, Franka, 1974-; Csokas, Marton, 1966-; Gaita, Raimond, 1946- (New York, NY : Magnolia Home Entertainment, 2008)
While his unhappy wife takes frequent trips away from home, Romulus, an immigrant farmer and blacksmith in Australia, struggles to keep his life together for his son.
Based on the memoir by Raimond Gaita.
Originally released as a motion picture in 2007.
Features: "Making of Romulus," deleted scenes, storyboards.
Eric Bana, Franka Potente, Marton Csokas, Kodi Smit-McPhee.
MPAA rating: Not rated.
DVD.
Keywords: Gaita, Raimond, -- 1946- -- Film and video adaptations; Fathers and sons -- Drama; Dysfunctional families -- Drama; Australia -- Social life and customs -- Drama; Motion pictures, Australian; Video recordings for the hearing impaired; Fiction films; Based on the book; Feature films; Biographical films; Foreign films